2019
DOI: 10.3847/2041-8213/ab4792
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Seismology of Quiet Solar Active Regions

Abstract: The ubiquity of recently discovered low-amplitude decayless kink oscillations of plasma loops allows for the seismological probing of the corona on a regular basis. In particular, in contrast to traditionally applied seismology which is based on the large-amplitude decaying kink oscillations excited by flares and eruptions, decayless oscillations can potentially provide the diagnostics necessary for their forecasting. We analysed decayless kink oscillations in several distinct loops belonging to active region … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 47 publications
3
32
1
Order By: Relevance
“…Kink oscillations are used for estimating the absolute value of the magnetic field (e.g., Nakariakov and Ofman 2001) and its variation along the loop (Verth and Erdélyi 2008), the spatial scale of the density stratification (e.g., Andries et al 2005), and give information about transverse profiles of the Alfvén speed and mass density (Aschwanden et al 2003), including its steepness (Pascoe et al 2016b). More recently, it was demonstrated that the ubiquitous kink oscillations observed in coronal active regions during the quiet time periods, allow for the seismological mapping of the Alfvén speed and magnetic field (e.g., Anfinogentov and Nakariakov 2019). Kink oscillations in loops of the sigmoid shape have been shown to carry the information about the free magnetic energy associated with non-potential field geometry (e.g., Magyar and Nakariakov 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kink oscillations are used for estimating the absolute value of the magnetic field (e.g., Nakariakov and Ofman 2001) and its variation along the loop (Verth and Erdélyi 2008), the spatial scale of the density stratification (e.g., Andries et al 2005), and give information about transverse profiles of the Alfvén speed and mass density (Aschwanden et al 2003), including its steepness (Pascoe et al 2016b). More recently, it was demonstrated that the ubiquitous kink oscillations observed in coronal active regions during the quiet time periods, allow for the seismological mapping of the Alfvén speed and magnetic field (e.g., Anfinogentov and Nakariakov 2019). Kink oscillations in loops of the sigmoid shape have been shown to carry the information about the free magnetic energy associated with non-potential field geometry (e.g., Magyar and Nakariakov 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside those larger-amplitude decaying oscillations, a second category of low-amplitude, transverse waves occurring in coronal loops has also been observed in recent years. These waves were first detected by Wang et al (2012) and Tian et al (2012), and were proven to be omnipresent in active region coronal loops (Anfinogentov et al 2013(Anfinogentov et al , 2015, making them possible tools for coronal seismology (Anfinogentov & Nakariakov 2019;Yang et al 2020). These decay-less oscillations have a near constant amplitude over the course of many periods, with frequencies equal to that of the fundamental standing kink mode (Nisticò et al 2013), as well as its second harmonic (Duckenfield et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar oscillations are detected as persistent Doppler-shift oscillations at loop apexes (Tian et al, 2012;Li et al, 2018). Anfinogentov, Nisticò, and Nakariakov (2013) demonstrated the ubiquity of decayless kink oscillations of coronal loops, which opens up interesting perspectives for regular seismological probing of the magnetic field in coronal active regions (Anfinogentov and Nakariakov, 2019). Of special interest is the diagnostics of the magnetic-field sigmoidity (Magyar and Nakariakov, 2020), and the related free magnetic energy.…”
Section: Introductionmentioning
confidence: 74%